Partnership for combating social exclusion, on the example, the Subcarpathian social cooperative - Szluz, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Social exclusion is associated with situations, in which an individual cannot normally participate in the activities of citizens in a given society. It is essential to note that such a restriction is not due to internal beliefs, but is beyond the control of that person. Societal exclusion is a multidimensional phenomenon, meaning, that a person cannot participate in political, economic and cultural life as a result of a lack of access to resources, goods and institutions, as well as restrictions of social rights or a deprivation of needs. The groups or social categories in which individuals are most vulnerable to exclusion are: the disabled, the mentally ill, addicts, the long-term unemployed, individuals with low professional skills, those released from correctional facilities, single mothers raising children, victims from pathological families, children and youth from neglected environments or raised outside of the family, the elderly, the homeless, immigrants, and members of ethnic minorities. The cause or effect of social exclusion is poverty. A combination of several of these noted problems increases the risk of experiencing exclusion. In the field of social assistance, the problems which an individual and their family experience are the stimuli or task for action to be taken. J. Wygnański stated that, with respect to clients, they are: (…) often those for which the existing instruments of social assistance or labour offices do not work. For many, it is not assistance, just control, and they do everything to dodge it. Some have limited their aspirations to the level of their existence, i.e. the necessity to earn money to purchase the cheapest alcohol. Can you reach such people with the tale of the fishing rod and fish? They are fixated on fish, not even salmon, but anything. They do not believe in a chance for independence, but they know how to navigate in the system of assistance offered by the state and non-governmental organizations, to receive something. Hence the need for new ideas for assistance – so that these people will be willing to help themselves. We are not the only one in Europe that has managed to create a welfare system perpetuated on passivity and exclusion, making it impossible for the welfare state to bear (Mateja 2008). The cited formulation indicates that long-term use of benefits generates the formation of a dependency on assistance. Effective social assistance should therefore be orientated towards activating, and cannot be deactivating and overwhelming. In the context of the aforementioned social exclusion, social enterprises which perform different functions have important tasks to fulfill. Social economy or social entrepreneurship are terms referring to social economy, combining both social and economic objectives. Competences mentioned in the catalogue of social enterprise: social integration and activity in the labour market, provision of public services: social (educational, custodial care, in the field of healthcare) and technical (of a reciprocal nature, in the open labour market, the supply of public goods and the development of local communities, and business and production activities) (Co to jest ekonomia społeczna?; Szluz 2010: 257-273). A specific form of social enterprise is a social cooperative which is mainly made up of individuals at risk of social exclusion due to unemployment, a disability or mental illness, or having trouble finding work. Activity and work in social cooperatives gives them a chance of social and professional activation, integration, as well as upgrading their skills. Unlike other social economy entities, the social cooperative requires a high degree of independence and responsibility from its members. A collegial method of decision making applies. Members of the cooperative are entirely responsible for the cooperative’s affairs, and learn independence and long-term planning. They care about the financial aspects, manage their own business, and set the direction of development. The cited issues have become the impetus for undertaking analysis and considerations, whose aim is to demonstrate cooperation for combating social exclusion. The Subcarpathian social cooperatives have become very good examples, which arose as a result of actions taken within the scope of the partnership.
Keywords: social cooperative; partnership; social exclusion